Indicadores visuais da qualidade do solo: subsídios para um guia prático ao agricultor familiar - Oliveira, Jessica Gomes Siqueira de (Universidade Federal de São Carlos, 2025)
Soil quality is essential for the sustainability of ecosystems and the maintenance of productive systems, and is directly influenced by use and management. Visual indicators have emerged as practical, accessible, and low-cost tools, providing rapid diagnoses of the physical, chemical, and biological conditions of the soil. This study aimed to select and evaluate the sensitivity of these indicators under different types of use or management in the Sorocaba and Middle Tietê River Basin and organize the information into a practical guide for family farming. Three environments with different use pressures were examined—native forest (MT), agroecological agroforestry system (SAF), and degraded pasture (PAST)—located in the municipality of Araçoiaba da Serra (SP). The visual analysis considered indicators such as color and odor, compaction, infiltration, root development, susceptibility to erosion, presence of macrofauna and litter, stoniness, soil cover, and effervescence in hydrogen peroxide. These indicators were complemented by laboratory parameters, enabling greater precision in interpreting sensitivity to management practices. The results demonstrated that the visual indicators clearly respond to the differences between the evaluated systems, showing strong complementarity with the laboratory analyses, especially those related to organic matter and soil structure. Visual and analytical indicators showed sensitivity to usage pressures, clearly distinguishing between environments: native forest showed better quality, SAF indicated consistent recovery under agroecological management, and pasture showed marked physical and biological degradation. Visual methods proved to be efficient, fast, and low-cost, establishing themselves as effective tools for monitoring soil quality and expanding diagnostic capacity in contexts with limited resources. Based on these results, the illustrated guide “Visual Diagnosis of Soil Quality: A Practical Guide for Family Farmers” was developed, which systematizes field procedures, facilitates their application by producers, and encourages the adoption of conservation practices.
Visual soil indicators: subsidies for a practical guide for family farmer
Keywords: Qualidade do Solo; Manejo Conservacionista; Pastagem; SAF; Manual Ilustrado; Soil Quality; Conservation Management; Pasture; Agroforestry System; Illustrated Manual; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; 2. Fome Zero e Agricultura Sustentável